LAS ADAPTACIONES DE GIL DE LOS CLÁSICOS LITERARIOS EN LOS SETENTA: UN RETORNO A SUS ORÍGENES - Juan Ignacio VALENZUELA MORENO, (Fonseca, Journal of Communication, 2023)
The flexibility of censorship and the desire to make a film qualité led many of our filmmakers to adapt various works of renowned Spanish writers in the early seventies. Rafael Gil was one of the directors who chose this new wave, mainly due to his passion for literature and his intention to return to its roots as a director, after a few years spent in a commercial cinema in which had lost the favour of the criticism. Thus, from 1971-1974 he directed four films in which he shall record their real inquisitiveness as a filmmaker.